Field notes contributed by Douglas C. Harr, February 25, 1983 - Harr, Douglas C.et al (1983)
Winter report of birds found in northwest Iowa contributed by Douglas C. Harr, February 25, 1983. Also included is a note from Harr to Thomas H. Kent regarding the increase in visibility of normal winter birds possibly due to a mild winter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1982-1983. Epson - sheet feed